Pengaruh Terapi Akupresur Terhadap Intensitas Nyeri Persalinan : Systematic Literature Review - Nova Yulita; Nova Avianti Rahayu (As-Shiha: Jurnal Kesehatan, 2022)
Labor pain needs to get good treatment and not cause complications that can interfere with labor. There are several techniques to reduce labor pain, namely pharmacological and non-pharmacological. Acupressure is a healing technique by pressing, massaging, massaging parts of the body to activate the circulation of vital energy or qi. Acupressure is also called needleless acupuncture, or acupuncture massage, because of the theory of acupuncture that forms the basis of the practice of acupressure. The purpose of this systematic literature review is to find evidence based on the effect of acupressure on the intensity of labor pain. This research method uses a systematic literature review approach and there are eight stages used in this review, namely identifying midwifery problems, priority problems and research questions, primary and secondary data frameworks, identification of relevant studies, prism flow diagrams, critical appraisal, data analysis and extraction. data. This review uses 2 databases with a period from 2010-2020. The total articles obtained were 402 articles, 12 articles were selected for review. Several articles compared the intensity of labor pain in the acupressure intervention and non-intervention groups and it was found that acupressure is an effective non-pharmacological pain management method for reducing labor pain. The conclusion of this study is that acupressure has an effect on reducing the intensity of labor pain.